Evolution and challenges of sustainability reporting in the banking sector: A systematic literature review - Ad\~ao M. Sebasti\~ao; Maria C. Tavares; Graça Maria do Carmo Azevedo (Administrative Sciences, 2024)
The objective of this study is to present an overview of sustainability reporting in the financial industry between 2016 and 2024, carrying out a systematic review of the literature on the topic in the banking sector. The theoretical framework addresses the integration of sustainability from the perspectives of stakeholders, agency and legitimacy theories, highlighting the interrelationship between financial practices and social responsibility. The research used quantitative and qualitative methods, focusing on a systematic review of the literature, analyzing databases such as Scopus and Web of Science in 116 articles. The results showed an annual publication growth rate of 29.68%, with an emphasis on environmental and social sustainability practices. The dissemination of knowledge about sustainability in the banking sector remains low. The central themes included sustainability disclosure, circular economy and FinTechs. Limitations in regulations and the lack of adequate regulations in developing countries, especially in Latin America and Africa, make it difficult to effectively implement these practices, highlighting the need for greater supervision and awareness. This study highlights that the sustainability disclosure in the banking context is a topic that still lacks sufficient exploration.
Keywords: 350; disclosure; banking industry; banking sector; reporting; sustainability